NOVEL AVIAN PARAMYXOVIRUSES AMONG WILD BIRDS IN KAZAKHSTAN - Kydyrmanov , A.I.; Sayatov , M.Kh.; Karamendin , K.O.; Fereidouni , S.; Kasymbekov , Ye.T.; Seidalina , A.B.; Daulbaeva , K.D.; Han , Ye.Ya.; Suleimenova , S.A. (Eurasian Journal of Applied Biotechnology, 2018)
This article presents the results of paramyxovirus monitoring in the avifauna of Kazakhstan from 2002 - 2015. New data were obtained on the epidemiology, evolutionary variability and phylogenesis of paramyxoviruses. Seventy paramyxovirus isolates belonging to serotypes PMV-1, PMV-4, PMV-6, PMV-8, PMV-13, PMV-16 and PMV-20 were isolated from feral birds in Kazakhstan. Viruses were isolated from 23 avian species belonging to six families in five orders: Anseriformes (swans, geese, and ducks), Charadriiformes (snipes and gulls), Falconiformes (eagles), Columbiformes (doves and pigeons), and Passeriformes (crows). Novel results showed that avian paramyxoviruses PMV-13 and PMV-20 were phylogenetically distant from each other and from the other serotypes. They formed separate branches showing different evolutionary origins from other circulating viruses in the territory of the Republic. These findings form an essential part of the study of avian viral biology and provide insight into methods for control and prevention of viral infections in avifauna. Viral monitoring should be carried out on an ongoing basis.